Music – source of immense joy or of disturbing frustration? - Mălăncioiu, Gabriel (Revista Vórtex, 2020)
In this essay we highlight the importance of the complementarity between an uninhibited vision, in which music is approached from a perspective that implies overcoming our cultural conditioning, and a vision that implies the integration of the cultural conditioning coming from the past. In the first part of the essay there are general references to the musical phenomenon, bringing into light aspects related to the compositional process later on. Finally, I discuss the importance of a holistic approach that encompasses polarities in education – in the field of music composition studies.